Peran Media Sosial Dalam Mempromosikan Ekonomi Kreatif Berbasis Tenun Di Desa Sukarara, Kabupaten Lombok Tengah - Asih P. Fitri; Khaeratun Hisan; Zulhaj Febrianti; Rohmayani Jalisna; Feby A. Wulan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Sukarara Village, Central Lombok Regency. Sukarara Village is known for its production of traditional woven fabrics that have high cultural and economic value. However, the main challenges faced are limited market access and low interest of the younger generation to preserve weaving skills. In this context, social media offers an effective solution to expand the promotional reach of woven products. Through platforms such as TikTok and Facebook, weaving artisans can showcase their products visually and interactively to a global audience. This research uses a qualitative approach with a netnography method to understand the interactions and digital marketing strategies used by local communities. The data sources studied were weaving craftsmen and weaving resellers. Data were collected through interviews, observation and documentation. Data analysis was carried out by collecting data, reducing data, presenting data, and conclusions. The instruments used were interview guidelines, observation guidelines, and documentation. Data validity was carried out by triangulating data, sources and techniques. The results showed that social media not only increased the visibility and sales of woven products but also helped in preserving local cultural heritage. TikTok, with its short video and live streaming features, proved particularly effective in attracting consumer attention and facilitating direct interaction. This research also reveals how local agents can modify and enrich social and economic structures through the use of social media, in line with Giddens' theory of structuration. For long-term sustainability, additional strategies to attract the younger generation and diversification of promotional platforms are required.